Increased Productivity through Dynamic Process Optimization in Sterile Facility 303 at Novartis Pharma Stein AG - Peter Nyfeler; Antonio Zeoli; Cédric Bokalota; Roland Chatelain (CHIMIA, 2004)
Pharmaceutical production processes are subject to a multiplicity of regulatory requirements regarding the product quality. Since economic aspects (e.g. productivity) also have to be considered, process optimizations have to be carried out. In Building 303 at Novartis Pharma Stein AG new technologies have been implemented, which are constantly reviewed and optimized to increase the productivity and to keep up with the state of the art and the requirements.